Functionally Relevant Maculopathy and Optic Atrophy in Spinocerebellar Ataxia Type 1. Issue 5 (6th May 2020) - Oertel, Frederike Cosima; Zeitz, Oliver; Rönnefarth, Maria; Bereuter, Charlotte; Motamedi, Seyedamirhosein; Zimmermann, Hanna G.; Kuchling, Joseph; Grosch, Anne Sophie; Doss, Sarah; Browne, Andrew; Paul, Friedemann; Schmitz‐Hübsch, Tanja; et al.
Abstract: Background: Spinocerebellar ataxia type 1 (SCA‐ATXN1) is an inherited progressive ataxia disorder characterized by an adult‐onset cerebellar syndrome combined with nonataxia signs. Retinal or optic nerve affection are not systematically described. Objectives: To describe a retinal phenotype and its functional relevance in SCA‐ATXN1. Methods: We applied optical coherence tomography (OCT) in 20 index cases with SCA‐ATXN1 and 22 healthy controls (HCs), investigating qualitative changes and quantifying the peripapillary retinal nerve fiber layer (pRNFL) thickness and combined ganglion cell and inner plexiform layer (GCIP) volume as markers of optic atrophy and outer retinal layers as markers of maculopathy. Visual function was assessed by high‐ (HC‐VA) and low‐contrast visual acuity (LC‐VA) and the Hardy‐Rand‐Rittler pseudoisochromatic test for color vision. Results: Five patients (25%) showed distinct maculopathies in the ellipsoid zone (EZ). Furthermore, pRNFL ( P  < 0.001) and GCIP ( P = 0.002) were reduced in patients (pRNFL, 80.86 ± 9.49 μm; GCIP, 1.84 ± 0.16 mm 3 ) compared with HCs (pRNFL, 97.02 ± 8.34 μm; GCIP, 1.98 ± 0.12 mm 3 ). Outer macular layers were similar between groups, but reduced in patients with maculopathies. HC‐VA ( P = 0.002) and LC‐VA ( P  < 0.001) were reduced in patients (HC‐VA [logMAR]: 0.01 ± 010; LC‐VA [logMAR]: 0.44 ± 0.16) compared with HCs (HC‐VA [logMAR]: –0.12 ± 0.08; LC‐VA [logMAR]: 0.25 ± 0.05). Color vision was abnormal in 2 patients with maculopathies. Conclusions: A distinct maculopathy, termed EZ disruption, as well as optic atrophy add to the known nonataxia features in SCA‐ATXN1. Whereas optic atrophy may be understood as part of a widespread neurodegeneration, EZ disruption may be explained by effects of ataxin‐1 gene or protein on photoreceptors. Our findings extend the spectrum of nonataxia signs in SCA‐ATXN1 with potential relevance for diagnosis and monitoring.